2021
DOI: 10.3390/biomedicines9091103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frailty on Hippocampal Volume in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Brain frailty may be related to the pathophysiology of poor clinical outcomes in chronic obstructive pulmonary disease (COPD). This study examines the relationship between hippocampal subfield volumes and frailty and depressive symptoms, and their combined association with quality of life (QOL) in patients with COPD. The study involved 40 patients with COPD. Frailty, depressive symptoms and QOL were assessed using Kihon Checklist (KCL), Hospital Anxiety and Depression Scale (HADS), and World Health Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The detailed scanning parameters have been described previously [30]. The volumes of hippocampal subfields were obtained using FreeSurfer software (version 6.0, https://surfer.nmr.mgh.harvard.edu/), which is widely used for patients with neuropsychiatric disease [41][42][43] and somatic disorder [44,45]. In the first step, "recon-all" processing was conducted in FreeSurfer.…”
Section: Magnetic Resonance Imaging Data Acquisition and Processingmentioning
confidence: 99%
“…The detailed scanning parameters have been described previously [30]. The volumes of hippocampal subfields were obtained using FreeSurfer software (version 6.0, https://surfer.nmr.mgh.harvard.edu/), which is widely used for patients with neuropsychiatric disease [41][42][43] and somatic disorder [44,45]. In the first step, "recon-all" processing was conducted in FreeSurfer.…”
Section: Magnetic Resonance Imaging Data Acquisition and Processingmentioning
confidence: 99%
“…Frequent exacerbator LABA, LAMA, ICS, roflumilast, macrolides Optimisation of comorbid physical and mental health conditions [27] Chronic bronchitis Roflumilast, mucolytics Use of CFTR modulators [13] Emphysema Lung volume reduction surgery Correction of miR overexpression [8] Type 1 respiratory failure Long-term oxygen therapy Increased vigilance for VTE in acute illness [29] Type 2 respiratory failure Domiciliary NIV Consideration of comorbidities such as OSA/ORRF [21] Eosinophilic COPD Steroids Identification of distinct microbiome in eosinophil-predominant COPD [15] Investigation of immunomodulatory alternatives to steroids [30] Bronchiectasis Targeted antibiotics, chest physiotherapy Identify severity clusters using biomarkers, to stratify follow-up and hospitalisation [33] α-1 antitrypsin deficiency LABA, LAMA, ICS α-1 antitrypsin augmentation therapy [17] Subgroups requiring further study Biomass and pollutant COPD Removal of pollutant exposure Use of predictive machine-learning to target individuals at greatest risk of pollutant-induced emphysema [31] Premalignant COPD Smoking cessation…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
“…Takahashi et al present an observational study exploring the relationship between hippocampal volume and clinical outcomes in patients with COPD [ 21 ]. Frail stable-state COPD patients and those reporting poor QoL were identified to have smaller estimated hippocampal volume via magnetic resonance imaging.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…For example, it has been reported that reduced lung function in early adulthood is associated with heart failure, arrhythmia, stroke, COPD, and obesity in the future [ 2 , 3 , 4 , 5 ]. Among them, COPD prevalence has been growing worldwide, an COPD can lead to physical inactivity, frailty, cognition issues, and mortality [ 6 , 7 , 8 , 9 ]. In addition to therapeutic drugs, approaches tailored to the characteristics of comorbidities, such as bronchiectasis, asthma, heart failure, sleep apnea, malnutrition, and frailty, have been shown to be viable in the management of COPD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%